A NEW METHOD FOR DISK LOW CYCLE FATIGUE LIFE PREDICTION - SHANG TiSong; ZHAO Ming; ZHANG Meng (Jixie qiangdu)
Low cycle fatigue failure is the main failure form of disks. In order to find a more accurate and reliable method to predict disks’ low cycle fatigue life,a correction life prediction model that describes the relation between Walker equivalent strain parameter and fatigue life was proposed based on the formula of three-parameter power function. The low cycle fatigue experimental data of 1Cr11Ni2W2 Mo V,GH4133,TC4 and TC11 materials at different conditions was simulated by the correction life prediction model and found the fitting curves can well describe the relation between Walker equivalent strain and fatigue life,and the life forecasting points are all in the 2 scatter band. In addition,using different methods to predict its life of high pressure compressor disk I at 60℃ and compared them with the experimental result. The results show that the correction model has a higher prediction accuracy than the other three models,its prediction value is 1048 that is close to the experimental value 1340 and the relative error is only- 21. 8%,moreover,this correction model can consider the influence on fatigue life that brought by the mean stress‘s change and provide a reference method for aircraft engine disks’ low cycle fatigue life prediction.